Paradox as Means of Expression of Author’s Ideological Position in Dramas of V. Vynnychenko and B. Shaw - Semak, O. (Journal of Vasyl Stefanyk Precarpathian National University, 2015)
The article has the comparative study of the phenomenon of paradox in the plays of the Ukrainian playwright V. Vynnychenko and English dramatist B. Shaw. It pays attention to the possibilities of paradox to express the author’s idea most exactly. This work has the analysis of two types of paradox – phraseological one and paradox on the level of the plot and their specific features.